2018
DOI: 10.1021/acscatal.8b03520
|View full text |Cite
|
Sign up to set email alerts
|

Hole-Selective CoOx/SiOx/Si Heterojunctions for Photoelectrochemical Water Splitting

Abstract: Cobalt oxide (CoO x ), an earth-abundant and low-cost oxygen evolving catalyst (OEC), has notable advantages as a top protection layer of photoanodes for solar-driven water oxidation because of its desirable durability. However, cobalt oxides exist as various phases, such as Co(II)O, Co2(III)O3, Co3(II,III)O4, and the (photo)­electrochemical properties of CoO x are significantly governed by its phase. Atomic layer deposition (ALD) is a suitable method to form a multifunctional layer for photoelectrochemical (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 68 publications
(114 reference statements)
1
43
0
Order By: Relevance
“…In addition, it was reported that the role of cobalt oxide in PEC water splitting can be engineered by ALD temperature. Oh et al observed that CoO grown at a low temperature (150 °C) could be used to build a hole‐selective heterojunction with n‐Si, and Co 3 O 4 formed at a high temperature (300 °C) acted as an efficient catalyst for the OER . On this basis, they constructed a SiO x /n‐Si photoanode loaded with a double‐layered ALD CoO x film (CoO and Co 3 O 4 ), which exhibited a J sc of 3.5 mA cm −2 , a value twofold higher than that of the CoO‐modified SiO x /n‐Si photoanode.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was reported that the role of cobalt oxide in PEC water splitting can be engineered by ALD temperature. Oh et al observed that CoO grown at a low temperature (150 °C) could be used to build a hole‐selective heterojunction with n‐Si, and Co 3 O 4 formed at a high temperature (300 °C) acted as an efficient catalyst for the OER . On this basis, they constructed a SiO x /n‐Si photoanode loaded with a double‐layered ALD CoO x film (CoO and Co 3 O 4 ), which exhibited a J sc of 3.5 mA cm −2 , a value twofold higher than that of the CoO‐modified SiO x /n‐Si photoanode.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
“…The use of ALD for electrocatalyst synthesis was recently summarized in a book chapter . These features make ALD a promising technique to deposit various electrocatalysts, e.g., Pt NPs, cobalt oxide, nickel oxide, and molybdenum sulfide, on the surface of different semiconductors to enhance the PEC water‐splitting performance.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…222 In the eld of electrocatalysis various suldes, phosphides, nitrides, oxides and (oxy)hydroxides are common catalysts, which are deposited on a substrate that serves as the electrode and they enhance either or both the activity and stability (for example, due to higher stability than the Si substrate in a strong alkaline environment). [223][224][225][226][227] A common starting high-specic-surface-area metallic substrate is nickel foam (NF), on which gas-phase electrodeposition and a variety of solvothermal reactions are used to deposit the metallic catalyst. Various redox catalysts were deposited on NF such as binary Ni-based materials, e.g., Ni 2 P, 228 Mo-doped Ni 2 P, 229 ternary amorphous tungsten-doped Ni x P, 228 or multiphase nickel suldes, 230 taking advantage of the abundant Ni surface.…”
Section: Transition-metal-nonmetal Compounds and Other Materialsmentioning
confidence: 99%
“…Nevertheless, these benefits are counterbalanced by various disadvantages, including low conductivity, serious charge recombination originating from high structural and surface defects, and sluggish OER kinetics . To overcome these issues, a number of strategies have been employed, such as design of nanostructured architecture, intrinsic and extrinsic doping, and heterojunction construction . These strategies can significantly suppress the recombination that occurs in the bulk, thus improving the PEC activity.…”
Section: Introductionmentioning
confidence: 99%